La didactique des langues : les relations entre les plans psychologique, linguistique et pédagogique - Germain, Claude; Netten, Joan (Linguarum Arena, 2018)
This article examines the relationship amongst the three fundamental aspects of second language teaching: psychological (language acquisition), linguistic (language content to be learned), and pedagogical (teaching strategies to be used). By studying the relationship amongst these three aspects in two different situations, the current approach to SL teaching and a new approach based on the neurological theory of Paradis (2004, 2009), the authors demonstrate that it is the beliefs held about the psychological aspect which governs the choice of pedagogical strategies. Further, the authors argue the crucial role that the psychological aspects of language acquisition plays in determining effective teaching strategies has been neglected by theorists, as shown for example by Un niveau seuil in the 1970’s and Le cadre européen commun de référence pour les langues (2000). The authors conclude that this lacuna has prevented the development of a truly effective pedagogy for teaching L2 communication skills, and that, in order to make any significant advance in the field, the psychological aspect must be integrated into the discussion of language teaching as a basis for the conceptualization of theoretically sound linguistic and pedagogical components.